Management of maxillary labial frenum with comparison of conventional and incision below the clamp techniques: a case report - Hasanuddin Thahir; Arni I. Djais; Shek Wendy; Muhammad H. Achmad; Fuad H. Akbar (Journal of Dentomaxillofacial Science, 2018)
Objective: Describes and compare the procedure of superior labial frenum frenectomies with conventional technique and incision below the clamp technique.Methods: Two female patient came to Departement of periodonsia, Unhas Dental Hospital to have frenectomies. The first patient was 28 year old with labialis superior frenulum reached attached gingiva, gingival recession 1-2 mm with calculus deposits, and referred to do frenectomy with Incision below the Clamp. While the second patient was 15 year old with labialis superior frenulum extend up to palatine papilla, central diastema and referred to do frenectomy with conventional technique.Results: The conventional techniques is done by engaged the frenum by a haemostat that inserted into the depth of the vestibule, and incision were placed on the upper and the under surface of haemostat, then followed by suturing the wound and periodontal pack. Insision below the clamp technique is done by placing a hemostat in position adjacent and parallel to the lip mucosa, and incision carried out below the clamp, then followed by suturing at the mucolabial fold and periodontal pack.Conclusions: Patients were very satisfied with the results that achieved. Technique Incision below the Clamp is an alternative treatment with good aesthetic and less bleeding during frenectomies by using a scalpel.